UJI IN VITRO NILAI SUN PROTECTING FACTOR (SPF) EKSTRAK ETANOL DAN EKSTRAK HEKSANA DAUN KENIKIR (Cosmos caudatus Kunth.) - Rahmi, Lisa Amelia; Emelda, Emelda; Solikah, Wahyu Yuliana; Rais, Ichwan Ridwan (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Bioactive substances found in kenikir leaves may be used as sunscreens. The purpose of the study is to evaluate the kenikir leaf ethanol extract (EEDK) and hexane extract (EHDK) as potential sunscreens. The maceration method is used for extraction, and 70% ethanol and n-hexane are used as each solvent. employing the UV-Vis spectrophotometric method at a wavelength of 290–400 nm and concentration series of 200, 400, 600, and 800 ppm to measure the SPF value of EEDK and EHDK. With SPF values of 1.3896 ± 0.0343, 1.7936 ± 0.0144, 2.2282 ± 0.0580, and 3.2575 ± 0.2257 obtained at concentrations of 200 ppm, 400 ppm, 600 ppm, and 800 ppm, respectively, the results demonstrate the potential of EEDK as a sunscreen. 1.1454 ± 0.0204; 1.3193 ± 0.0048; 1.4993 ± 0.0169 are the EHDK SPF values.